2004
DOI: 10.1029/2004ja010478
|View full text |Cite
|
Sign up to set email alerts
|

On magnetic reconnection regimes and associated three‐dimensional asymmetries: Hybrid, Hall‐less hybrid, and Hall‐MHD simulations

Abstract: [1] Magnetic reconnection in a plane current sheet is investigated in both two and three dimensions, using three different types of simulation codes, Hall MHD, hybrid (electron fluid, kinetic ions), and a new code called Hall-less hybrid. The latter code, which is similar to the hybrid code but has the Hall term removed, enables us to clarify the differences between kinetic ion and Hall MHD approaches. The major findings of this research are (1) Sweet-Parker regime of reconnection cannot be maintained and does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 46 publications
5
73
1
Order By: Relevance
“…Since far more particles are needed in the CAM-CL scheme to achieve the same degree of energy conservation as the predictor-corrector scheme the actual difference in CPU time needed by each scheme may not be that great. Karimabadi et al (2004) concludes that the CAM-CL method is not very suitable to applications in moving plasma. Both Karimabadi et al (2004) and Krauss-Varban (2005) concluded that under circumstances where high accuracy and the best conservation properties are required, the predictor-corrector method greatly outshines the CAM-CL method.…”
Section: Comparing the Schemesmentioning
confidence: 95%
See 1 more Smart Citation
“…Since far more particles are needed in the CAM-CL scheme to achieve the same degree of energy conservation as the predictor-corrector scheme the actual difference in CPU time needed by each scheme may not be that great. Karimabadi et al (2004) concludes that the CAM-CL method is not very suitable to applications in moving plasma. Both Karimabadi et al (2004) and Krauss-Varban (2005) concluded that under circumstances where high accuracy and the best conservation properties are required, the predictor-corrector method greatly outshines the CAM-CL method.…”
Section: Comparing the Schemesmentioning
confidence: 95%
“…Comparisons of the predictor-corrector and the CAM-CL schemes can be found in KraussVarban (2005) and Karimabadi et al (2004). When both schemes were run at the same time step they compared well on some tests.…”
Section: Comparing the Schemesmentioning
confidence: 96%
“…The coupled kinetic/magnetofluid tail model will allow resolution of the very poorly understood, complex, highly time dependent changes that the thinned cross-tail current sheet undergoes leading up to the onset of fast reconnection (Karimabadi et al 2004;Raeder et al 2010;Pritchett and Coroniti 2011;Sitnov and Schindler 2010;Sitnov and Swisdak 2011;Vapirev et al 2013). Once reconnection commences, this new tail model will allow the effects of the time dependent growth in the length of the X-line, only captured to date in highly restricted regions, upon the entire tail to be recovered.…”
Section: Study Of Magnetotail Reconnectionmentioning
confidence: 99%
“…Here the Hall term needs to be included, since otherwise momentum conservation is violated and no bulk force is exerted on the ions (Karimabadi et al, 2004).…”
Section: Numerical Modelmentioning
confidence: 99%